Validation of the name Semecarpus kathalekanensis (Anacardiaceae) - Kambale, Sharad S.; Kullayiswamy, Raja; Swaminath, Muduvadi H.; Sanjappa, Munivenkatappa (Phytotaxa, 2016)
During field surveys in Brahmakarmali (North Goa, India) we collected Semecarpus kathalekanensis Dasappa & Swaminath (2000: 78). In order to confirm the identity of the specimens, we examined the protologue and realized that the name Semecarpus kathalekanensis was not validly published, because the authors failed to indicate the herbarium in which the type is conserved (art. 40.7 of the ICN, McNeill et al., 2012). The authors, however, provided a Latin description and indicated a single gathering “10 Jan. 1998, Dasappa 758-WGP” as the holotype. They also cited “Dasappa 1865-WGP” and “Dasappa 1890-WGP” as paratypes. We traced the original material at the Herbarium of Karnataka Forest Department’s Research and Utilization Division, Doresanipalya, Bangalore (Office of the Additional Principal Chief Conservator of Forests, Karnataka). So, the name Semecarpus kathalekanensis is validated here by reference to the previously published description by Dasappa & Swaminath (2000) and by indicating the herbarium in which the holotype is conserved.